A face parda da “Conspiração dos Alfaiates”: homens de cor, corporações militares e ascensão social em Salvador no final do século XVIII - Mota, Celio de Souza (2010)
In the historiography, the Conspiracy of the Tailors " is a theme quite visited, however, some subjects still need to be deepened, as the color men's participation in the movement. He/she gave way, to present research it intended to contribute for that discussion leaving of the inquiry of the reasons that you/they took to the members of one of the instruments of repression of the Portuguese absolutist State, if they insert in the movement. Like this, the sedition of 1798 " was taken as privileged window of observation of the color men's world in Bahia of the end of the century XVIII, focusing the social tensions and the stigmata of the color presents in that society. By the analysis of the solemnities of the Judicial inquiry, crossing with letter-patents, solicitations of confirmation of patents and other documents, it was possible a " world to pull the curtain created " by the brown men; your aspirations and desires of social ascension saw militias. Your experiences originating from of your busy position in the colonial hierarchies of the society baiano took the brown men they build her/it sociabilities - however without forming a homogeneous social layer - in the breast of the military institutions, that rotated around an own political project. They intended to institute a Republic, a " government democratic ", that independent of color, it contemplated your longings. For so much, they formed an alliance with brown slaves, poor whites, segments of the economical and learned elite of the captaincy baiano, forming a heterogeneous group, with specific objectives demarcated by those distinctions. Your daring was worth them repression of the Portuguese State it lasts. But your ideals echoed.